Munasabah Qur-An Surah An-Nisa’ Ayat 7 Dan 8 Dengan Surah An-Nisa’ Ayat 11 Dan 12 Dalam Permasalahan Warisan Di Kecamatan Pulau Rakyat - Nurul Jumadissaniyah Sitorus; Dedi Masri; M. Alfiansyah; Nor Azwa (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
This journal reviews the problems that occurred in Pulau Rakyat District regarding the marital law contained in surah An-Nisa' verses 7.8 and 11.12. 'Ulumul Qur'an as one of the sciences in the study of the Qur'an has been well established since the 7th-9th century Hijriyah. Munasabah science (knowledge of the relationship between one sura/verse and another sura/verse) is part of the 'ulumul qur-an. This knowledge is quite urgent in order to make all the verses of the Qur'an as a unified whole. Starting from Az-Zarqashi's opinion that the Koran is not a word that was revealed by accident, by accident, and without a specific goal and purpose. Thus, every use and arrangement of words, construction of verses and surahs (munasabah) and the transition of themes contained therein have the power of the concept as a complete sentence. By using a qualitative research method that focuses on search libraries, the problem that is being discussed in this research becomes a complex matter. Where also presenting resource persons who know in this field. The population in this study are residents who lack knowledge of inheritance law. The results of the research data are presented in a descriptive form. The result is that 10 out of 12 samples have many problems related to inheritance law.